Adriana (Ship) certification - Adriana (Ship)
Certification (1804 September 29) of the ship Adriana for its voyage from the port of the city of New York to Liverpool, England.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ship's papers -- 19th century; Voyages and travels; Liverpool (England); New York (N.Y.)